2021
DOI: 10.1001/jamanetworkopen.2021.32388
|View full text |Cite
|
Sign up to set email alerts
|

Racial and Ethnic Disparities in the Use of Prostate Magnetic Resonance Imaging Following an Elevated Prostate-Specific Antigen Test

Abstract: IMPORTANCE Prostate cancer screening and diagnosis exhibit known racial and ethnic disparities.Whether these disparities persist in prostate magnetic resonance imaging (MRI) utilization after elevated prostate-specific antigen (PSA) results is poorly understood. OBJECTIVETo assess potential racial and ethnic disparities in prostate MRI utilization following elevated PSA results. DESIGN, SETTING, AND PARTICIPANTS This cohort study of 794 809 insured US men was drawn from deidentified medical claims between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 40 publications
0
15
1
Order By: Relevance
“…In lower income populations, White men had higher odds of receiving PSA monitoring versus Black men (OR, 1.15; 95% CI, 1.08–1.22) 68 . Among insured men who had elevated PSA results between 2011 and 2017, Black men were less likely to undergo subsequent prostate magnetic resonance imaging compared with White men 69 . In addition, in real‐world clinical practice, Black men were less likely to receive comprehensive genomic profiling earlier in their treatment course compared with men of European ancestry 70 .…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In lower income populations, White men had higher odds of receiving PSA monitoring versus Black men (OR, 1.15; 95% CI, 1.08–1.22) 68 . Among insured men who had elevated PSA results between 2011 and 2017, Black men were less likely to undergo subsequent prostate magnetic resonance imaging compared with White men 69 . In addition, in real‐world clinical practice, Black men were less likely to receive comprehensive genomic profiling earlier in their treatment course compared with men of European ancestry 70 .…”
Section: Observationsmentioning
confidence: 99%
“… 68 Among insured men who had elevated PSA results between 2011 and 2017, Black men were less likely to undergo subsequent prostate magnetic resonance imaging compared with White men. 69 In addition, in real‐world clinical practice, Black men were less likely to receive comprehensive genomic profiling earlier in their treatment course compared with men of European ancestry. 70 In contrast, another retrospective study of 3083 Black men and 1704 White men who underwent RP in multiple VA medical centers reported that Black men of low SES experienced a decreased risk of post‐RP castration‐resistant prostate cancer, metastasis, and PCSM versus White men.…”
Section: Observationsmentioning
confidence: 99%
“…They further confirmed that patients who lived in areas with a high education level and median household income ⩾$60,001 had a higher likelihood of receiving an mpMRI regardless of clinical presentation of disease. A recent study from Abashidze et al 48 further elucidated racial disparities among MRI utilization. From 2011 to 2017, MRI has in increasing utilization across all races.…”
Section: Cost Advantages and Socioeconomic Impactmentioning
confidence: 99%
“…A recent study from Abashidze et al. 48 further elucidated racial disparities among MRI utilization. From 2011 to 2017, MRI has in increasing utilization across all races.…”
Section: Introductionmentioning
confidence: 99%
“…9 Another recent study of nearly 800,000 commercially insured men undergoing a prostatespecific antigen test between 2011 and 2017 reported that Black and Hispanic patients were significantly less likely than White patients to undergo prostate MRI after receiving an elevated prostate-specific antigen test result, highlighting a need to better understand and mitigate physician decision-making biases and other potential sources of these disparities. 10 Most recently, the extension of such imaging disparities to modern molecular imaging tracers was demonstrated in a single U.S. tertiary medical center review of 1,756 patients: 1,502 receiving 68 Ga-PSMA-11 and 254 receiving 18 F-fluciclovine. Black patients had increased odds of receiving imaging with 18 F-fluciclovine versus 68 Ga-PSMA-11 compared with non-Hispanic White patients (odds ratio, 3.88; 95% CI, 1.90-7.91), and there were no other statistically significant differences across other demographic categories assessed.…”
Section: Health Disparities In Diagnostic Imaging and Radiotherapy Fo...mentioning
confidence: 99%